How does community density influence resident health? - White, Grant Leonard (Kansas State University, 2021)
Community density and public health have a long history that can be traced back to the birth of civilization. Across the world cities of different sizes can be drastically different in terms of overall public health, and this is primarily related to what the World Health Organization calls Indicators of health. They define health as “a state of complete physical, mental and social well-being”. Understanding how variations in density can influence the population’s overall health opportunities can benefit many future professionals across a broad spectrum of professions. This report brings both topics together to show how different variations in density can influence the overall health and well-being of the public. By defining three different density measurements and combining them with the Center for Disease Control’s “Social Determinants of health” we can get a clearer view of how density can impact opportunities for the public’s health outcomes.
Keywords: Health; Density; Community; Correlation